Developing and Testing a Local Expert-Based Reading Process for Use to Examine Discrepancies Between Guidelines and Current Clinical Practices - Cases, Cécile; Gallini, Adeline; Lafont Rapnouil, Stéphanie; Bougon, Emmanuelle; Mathur, Anjali; Brismontier, Ariane; Taib, Simon; Sporer, Marie; Arbus, Christophe; Salles, Juliette (Frontiers in Psychiatry, 2021)
The use of relevant guidelines is critical in psychiatric clinical practice to ensure global care homogeneity especially for care orientation. Identifying whether guidelines are successfully implemented for care referring as well as determining which factors could limit their implementation is critical, as such knowledge would enable pragmatic solutions to be set up to improve global care’s organization and, as a result, break down said obstacles in their implementation. However, the first step before exploring the limits for guidelines implementation consist in determining if they are or not applied in practice. We propose to evaluate the discrepancy between guidelines and current practice thanks to a reading process based on a panel of local experts who analyze medical files extracted from a database. We designed the reading process with a series of six standardized questions that the experts were required to answer. The method’s feasibility was tested in a clinical study about the use of relevant guidelines in our psychiatric ED concerning patients with Borderline Personality Disorder (BPD). The local experts read the medical files to determine if, in their judgement, the proposed care complied with the current BDP guidance. In this study the experts analyzed 333 medical files. The reading process revealed substantial agreement 0.85%; Fleiss Kappa - 0.69. We found that this result is promising and suggests that such method could be used in future protocols. Over more, this process is practical, reliable and required very few materials.